Revitalisasi Kawasan Pecinan Sebagai Pilar Integrasi Sosial Masyarakat Desa Karangturi - Seviana Widya Astuti; Gunawan Gunawan (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2025)
Karangturi Village has a community of various religions and ethnic differences, this diversity creates tolerance and acculturation in the community, many are found in buildings in the Chinatown area. This research aims to find out how building revitalization in maintaining the social integration of multicultural communities. This study uses Karl Marx’s commodification theory (Ritzer, 2012) with a qualitative research method of descriptive approach, data collection is carried out by observation, interviews, and documentation. The results of the study show that the revitalization of buildings as tourist destinations is carried out to maintain, preserve, and introduce buildings to the wider community inseparable from the role of community groups, namely, village governments, entrepreneurs, communities, pokdarwis, and the community. Various kinds of activities carried out by community groups are able to create integration between people of different religions and ethnicities through cooperative relationships between entrepreneurs and employees so that their business continues to run. In addition, cooperation is also carried out by communities, pokdarwis, village governments, communities, and other institutions. So that building revitalization not only preserves the building and obtains economic benefits, but is also able to maintain the integration of the Karangturi Village community.